The Development of an intelligent e-health Mobile Application in Indonesia: A Preliminary Study - Djawad, Yasser Abd; Suhaeb, Sutarsi; Mustakim, Ridwansyah; Jaya, Hendra; Ronge, Saharuddin; Sakka, Saliruddin (Universitas Lampung, 2019)
Telehealth has developed as an alternative to cover healthcare in all regions. Telehealth technology cannot be separated from Information and Communication Technology (ICT) that has been infiltrated to human activities nowadays. Internet and mobile phone technologies in Indonesia have become new major needs. Indonesian Government and some institutions have tried to use these technologies in healthcare services in some remote areas. However, some obstacles have been found in the implementation of the technologies such as inadequate ICT infrastructure and lack of policies about healthcare for remote areas. The study was conducted to obtain the recent status of the telehealth in Indonesia to develop a simple and proper mobile application. A literature study was conducted by collecting relevant information such as reports, regulations and policies released by the Indonesia Government regarding the healthcare infrastructures and latest technology used for telehealth. In addition, updated information from various institutions was also collected. The study reveals that there has been a gradual increase in the number of healthcare infrastructures in some remote areas in Indonesia. The number of ICT infrastructures is also expected to increase every year to facilitate communities in remote areas to be connected with others. Therefore, a mobile model of telehealth using text message services would be designed as a development model based on previous models that have been designed by some researchers.